Activated reaction synthesis of silicon oxynitride from silica and silicon nitride. Issue 7 (May 2018) - Fruhstorfer, Jens; Kerber, Florian; Weigelt, Christian; Moritz, Kirsten; Aneziris, Christos G.
Abstract: This study investigates the preparation of samples with equimolar parts of silica and silicon nitride and the subsequent reaction synthesis of silicon oxynitride. The influence of the raw material and the processing parameters on the conversion yield was analyzed. In detail, the effects of the silica crystallinity and of the grain size of the silicon nitride were investigated. Furthermore, the reaction synthesis was activated by magnesium hydroxide or calcium hydroxide. The samples were prepared by slip casting in plaster molds. Firstly, the optimal dispersant type, a synthetic polyelectrolyte, was determined. For the batches with the finer silicon nitride the measured optimal amount was 0.6 wt%. For the batches with the coarser silicon nitride it was 0.18 wt%. From the cast and demolded samples, broken pieces were fired at 1550 °C for 1, 8 or 15 h in nitrogen atmosphere. The conversion yield of silicon oxynitride was analyzed by quantitative X-ray diffraction. The fraction of silicon oxynitride increased with extended holding time at the sintering temperature, by the use of fine silicon nitride, and by the addition of magnesium hydroxide as sintering additive. The silica crystallinity had no statistically significant effect. The obtained maximum conversion yield was 92 wt%.